The Impact of Game-Based Learning Science for Kids on the Development of Logical Thinking in Children Aged 5-6 Years - Nur Fadilah, Siti; Fitri, Ruqoyyah; Matheos Lasarus Malaikosa, Yes; Kristanto, Andi; Dewi, Utari; Jannah, Miftakhul (Journal of Islamic Education Students (JIES), 2025)
This study aims to examine the effectiveness of game-based Learning Science for Kids in developing logical thinking skills in children aged 5-6 years. The study involved 17 children as subjects, with data collected through observation sheets. A quantitative approach was employed using an experimental method with a one-group pretest-posttest design, which analyzes the impact of an intervention under controlled conditions using the N-gain test. The results indicate that the average N-gain score obtained was 0.731, categorized as high (g > 0.7). These findings suggest that game-based Learning Science for Kids is highly effective in enhancing children's logical thinking skills. Therefore, this learning model can serve as an effective alternative for strengthening logical thinking abilities in children aged 5-6 years.